GEOMETRIC OPTIMIZATION OF “+”-SHAPED CAVITY USING CONSTRUCTAL THEORY - Avendaño, P. A.; Souza, J. A.; Adamatti, D. F.; Santos, E. D. dos (Revista de Engenharia Térmica, 2017)
In this work it is applied the Constructal Theory for the study of the geometry of an “+”-shaped isothermal cavity inserted in a conductive solid body. Main goal is to minimize the maximum temperature in the solid. The total volume of the solid and the total volume of the cavity are kept fixed while the dimensions of the cavity geometry vary according to constraints and degrees of freedom defined by the Constructal Design. The solid body has internal heat generation and its external surfaces are insulated. Cavity walls are isothermal with constant temperature Tmin. Obtained results indicate that the optimal performance of “+”-shape cavity is 37.2% better that the optimal performance of “C”-shape cavity and 10.8% better than the “T”-shaped cavity for the same thermal conditions.